2021
DOI: 10.1371/journal.pone.0257810
|View full text |Cite
|
Sign up to set email alerts
|

Force production and muscle activation during partial vs. full range of motion in Paralympic Powerlifting

Abstract: Paralympic Powerlifting is a sport in which the strength of the upper limbs is assessed through bench press performance in an adapted specific bench. It is therefore essential to optimize training methods to maximize this performance. The aim of the present study was to compare force production and muscle activation involved in partial vs. full range of motion (ROM) training in Paralympic Powerlifting. Twelve male athletes of elite national level in Paralympic Powerlifting participated in the study (28.60 ± 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 22 publications
0
24
0
2
Order By: Relevance
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
“…The electromyographic signals were captured using through double type electrodes positioned on the right side of the body in parallel to the muscle fibers, located 2 cm from the center at the point of the area of greatest muscle amplitude. The ground electrode was placed over the olecranon [ 2 , 13 , 14 ]. The area of skin used for electrode placement was shaved and cleaned with alcohol before the electrode fixation procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the subjects performed five repetitions with 40% of 1RM, followed by three repetitions with 50% of 1RM, one repetition with 70, one with 80, and one with 90% of 1RM. Between sets, participants rested for at least three minutes [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, regarding PP, studies have focused more on the health issues related to the etiology of injuries [ 8 , 35 ]. In PP, the extended legs on the bench tend to reduce the transfer of force to lifting [ 36 ], in which affects the maintenance of force, power, velocity, and, and these are not well elucidated [ 16 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%